Remarks on network public theory - Brol, Marcin; Czetwertyński, Sławomir (Managerial Economics, 2014)
This paper is a trial of capturing of a relation between traditional public sphere atrophy and the augmentation of a network public sphere. A thesis is advanced that the traditional public sphere is subject of the atrophy, however, the entire network public sphere is subject of the augmentation process. Such a formulated thesis forces a choice between two following issues. The first of them regards a relation between factors, which stimulate the atrophy and the augmentation. The second issue regards a role played by social media in the network public sphere. Considerations included in the paper are based on the public sphere theory of J. Habermas and on the M. Castells’ network society theory.